2022
DOI: 10.1161/jaha.121.023386
|View full text |Cite
|
Sign up to set email alerts
|

Moderate‐ and High‐Intensity Exercise Improves Lipoprotein Profile and Cholesterol Efflux Capacity in Healthy Young Men

Abstract: Background Exercise is associated with a reduced risk of cardiovascular disease. Increased high‐density lipoprotein cholesterol (HDL‐C) levels are thought to contribute to these benefits, but much of the research in this area has been limited by lack of well‐controlled subject selection and exercise interventions. We sought to study the effect of moderate and high‐intensity exercise on HDL function, lipid/lipoprotein profile, and other cardiometabolic parameters in a homogeneous population where ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Moreover, another study reported that daily exercise enhanced antioxidative activity of HDL in middle-aged women [50 ▪ ]. Consistent with these results, both moderate and intense exercise improved cholesterol efflux to HDL in young men [51 ▪ ]. Finally, in another study, both moderate and intense exercise was able to improve antioxidative capacity of HDL [52 ▪▪ ].…”
Section: High-density Lipoprotein and Energy Expenditurementioning
confidence: 52%
“…Moreover, another study reported that daily exercise enhanced antioxidative activity of HDL in middle-aged women [50 ▪ ]. Consistent with these results, both moderate and intense exercise improved cholesterol efflux to HDL in young men [51 ▪ ]. Finally, in another study, both moderate and intense exercise was able to improve antioxidative capacity of HDL [52 ▪▪ ].…”
Section: High-density Lipoprotein and Energy Expenditurementioning
confidence: 52%
“…Meanwhile, there is some evidence that aerobic exercise has a neutral effect on lowering triglyceride levels. 34 35 Although the impact of regular exercise on reducing atherosclerotic CVD risk is undeniable, 36 37 additional research in Korean databases is required to validate the impact of exercise on triglyceride levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increase in HDL-C quantity was not accompanied by the enhancement of HDL quality, such as increases in particle size and antioxidant ability. Healthy young men who completed a 12-week moderate-intensity exercise program as military soldiers [ 35 ] showed an elevation of HDL-C and apoA-I but without an increase in HDL particle size, even though their cholesterol efflux was enhanced. On the other hand, the anti-inflammatory properties of HDL were enhanced in these soldiers, but the antioxidant ability of HDL was not determined.…”
Section: Discussionmentioning
confidence: 99%